2018
DOI: 10.3389/fnins.2018.00645
|View full text |Cite
|
Sign up to set email alerts
|

Do Complexity Measures of Frontal EEG Distinguish Loss of Consciousness in Geriatric Patients Under Anesthesia?

Abstract: While geriatric patients have a high likelihood of requiring anesthesia, they carry an increased risk for adverse cognitive outcomes from its use. Previous work suggests this could be mitigated by better intraoperative monitoring using indexes defined by several processed electroencephalogram (EEG) measures. Unfortunately, inconsistencies between patients and anesthetic agents in current analysis techniques have limited the adoption of EEG as standard of care. In attempts to identify new analyses that discrimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
42
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 57 publications
6
42
5
1
Order By: Relevance
“…Specifically, we observed that initially spherical attractors became flattened and more ellipsoidal when moving from waking to loss of righting reflex (MacIver & Bland, 2014). We observed a similar change in attractor shape when characterizing human subjects anesthetized with a combination of remifentanil and nitrous oxide , and another patient population anesthetized with propofol and fentanyl (Eagleman, Vaughn, et al, 2018). We quantified the shape changes we observed using a novel geometric phase-space analysis, termed the ellipse radius ratio (ERR).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Specifically, we observed that initially spherical attractors became flattened and more ellipsoidal when moving from waking to loss of righting reflex (MacIver & Bland, 2014). We observed a similar change in attractor shape when characterizing human subjects anesthetized with a combination of remifentanil and nitrous oxide , and another patient population anesthetized with propofol and fentanyl (Eagleman, Vaughn, et al, 2018). We quantified the shape changes we observed using a novel geometric phase-space analysis, termed the ellipse radius ratio (ERR).…”
Section: Introductionmentioning
confidence: 80%
“…We fit the 3D attractor with an ellipsoidal solid of revolution (Khachiyan, 1980) and then calculated the ratio between the major and minor axes. This ellipse radius ratio changes significantly and consistently before and after loss and recovery of response during several anesthetic regimes (Eagleman, Vaughn, et al, 2018;. Additionally, the ERR also shows a significant difference in adult patients across a wide range of ages (Eagleman, Vaughn, et al, 2018;.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies with Propofol anesthesia showed a change in scale free behavior before and after loss of consciousness (Eagleman et al, 2018) and a difference between wakefulness and loss of consciousness as well as recovery from anesthesia (Tagliazucchi et al, 2016). Also with the help of entropy measures, Eagleman et al (2018) could show a change in complexity of scalp EEG data before and after loss of responsiveness in anesthesia patients. Similarly, Schartner et al (2015) could distinguish between loss of consciousness during Propofol induced anesthesia and wakeful rest by means of entropy measures as well as compressibility measures.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the measurement of this scale free behavior appears promising in the investigation of state transitions (Weiss et al, 2009). Studies with Propofol anesthesia showed a change in scale free behavior before and after loss of consciousness (Eagleman et al, 2018) and a difference between wakefulness and loss of consciousness as well as recovery from anesthesia (Tagliazucchi et al, 2016). Also with the help of entropy measures, Eagleman et al (2018) could show a change in complexity of scalp EEG data before and after loss of responsiveness in anesthesia patients.…”
Section: Introductionmentioning
confidence: 99%